Study on Error Pattern of Consonant of Children with Functional Dysarthria - Zhihong DU; Bingwei PENG; Siyuan YANG; Zhifang HUANG; Zhuoming CHEN (康复学报)
Objective:To study the distribution characteristics, error pattern and acquistion features of disordered consonants of children with functional dysarthria, so as to provide the theoretical guidance for the design of pronunciation rehabilitation programs.Methods:90 cases, including three age groups(4 years old, 5 years old and 6 years or older)of children with functional dysarthria were included in this study. The dysarthria examination scale from China Rehabilitation Research Center was applied to evaluate the error rate of consonants of six pronouncing parts(labial consonant, supradental consonant, blade-alveolar consonant, blade-palatal consonant, lingua-palatal consonant and velar consonant).Results:When all subjects were in one group, the error ratios of consonants of six pronouncing parts were 26.9%, 41.7%, 42.6%, 38.9%, 58.5% and 55.0%. When subjects were separated to three agegroups, the highest error rates of consonants were concentrated in lingua-palatal consonant and velar consonant(47.4%-70.7%), and the lowest error rate was concentrated in labial consonant(25.0%-32.8%). Among three kinds of consonants error pattern(substitution, omission, and distortion), the highest error rate was substitution. When all subjects were in one group, the substitution error rates of six pronouncing parts were 69.1%, 45.3%, 84.3%, 77.1%, 70.3% and 74.2% respectively;the omission error rate was highest when pronouncing supradental consonant(44.0%);the omission error rate was lowest when pronouncing lingua-palatal consonant(1.9%)and velar consonant(1.5%), but the distortion error rate was highest when pronouncing lingua-palatal consonant(27.5%)and velar consonant(24.2%).Conclusion:Whether the children with functional dysarthria at preschool or school age, the error rate of consonants is highest when pronouncing lingua-palatal consonant and velar consonant and lowest when pronouncing labial consonants, the main error pattern is the substitution. When pronouncing supradental consonant, the omission error happened most frequently;when pronouncing lingua-palatal consonant and velar consonant, the distortion error happens most frequently. The phonological acquisition of children under disease state is similar to normal children, and the error pattern is related to pronouncing part. When developing the rehabilitation program, the characteristics of disordered consonants should be considered.